European community and SAARC - K B Lall Ed and others; LAL (K B) Ed; CHOPRA (H S) Ed; MEYER (Thomas) Ed (New Delhi Radiant Publishers, 1993)
Revised version of papers contributed to a seminar on "European Union in 1992: its Significance for India and South Asia" organized by the West European Division of the School of International Studies, Jawaharlal Nehru University, New Delhi, in September 1990.
Keywords: Global Development; South Asia; Indo-Pakistan Relations